2018
DOI: 10.2217/cer-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frailty on resource use and cost for Medicare patients

Abstract: Frailty contributes greatly to cost of care, but while often correlated, is not synonymous with MCCs. Thus, it is important to control separately for frailty in studies that compare medical care use and cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 23 publications
(28 reference statements)
3
30
4
1
Order By: Relevance
“…The observed hospitalization rate (for all frailty types) in this study was much lower than that for several studies [19][20][21][22][23][24][25][26][27][28]. This nding reveals that elderly Malaysians are probably healthier than elderly in other countries.…”
Section: Discussioncontrasting
confidence: 75%
“…The observed hospitalization rate (for all frailty types) in this study was much lower than that for several studies [19][20][21][22][23][24][25][26][27][28]. This nding reveals that elderly Malaysians are probably healthier than elderly in other countries.…”
Section: Discussioncontrasting
confidence: 75%
“…56 Multiple studies using cohorts of community-dwelling older adults have showed that the health care costs of frail individuals are sometimes several-fold higher than those of non-frail counterparts. [57][58][59][60][61] Older adults form the main users of medical and social care services, 62 and the majority of health care costs are incurred by them. In the context of ongoing population aging, with an unprecedented growing number and proportion of older adults, this epidemiological and demographic population shift is starting to have a major impact on health care systems.…”
Section: Impacts Of Frailty On Health Care Systemsmentioning
confidence: 99%
“…Based on self-reported incidence of healthcare resource utilisation, cross-sectional studies in international literature have found frailty to be associated with an increased likelihood of general practice (adjusted odds ratios (OR): 2.1-4.4), specialist (OR 1.3-1.8), emergency department (OR 2.5-6.2) and inpatient (OR 2.1-3.3) service utilisation [8,[10][11][12]. These ndings were also supported by the results from prospective cohort studies [13][14][15] as well as panel studies [16].…”
Section: Introductionmentioning
confidence: 63%